Career Exploration as Social and Emotional Learning: A Collaborative Ethnography with Spanish Children from Low-Income Contexts - Soledad Romero-Rodríguez; Celia Moreno-Morilla; David Muñoz-Villaraviz; Marina Resurrección-Pérez (MDPI AG, 2021)
Children's career exploration is a critical aspect of career development. Through it, children explore the interplay between their different life roles, including those related to work (in a broad sense), learning, and education. Through career exploration, children can (re)construct the emotions derived from the interactions between personal and contextual factors by giving meaning to life experiences. This process involves cognitive and affective activities. Evidence suggests that children from low-income contexts are more likely to drop out of school and show lower educational aspirations. Providing career exploration interventions introduces an intentional learning that allows children to develop a higher level of career awareness and increase their aspirations for the future. The sample analyzed consisted of students between 6 and 8 years old from a low-income school in Seville (Spain). The data collection methods used have been those of collaborative ethnography (e.g., unstructured interviews, student productions, and photographs). Co-analysis was the chosen method for systematizing the information used in this research. Our results have revealed a system of influences which plays an important role in the different contexts and emotions that the children derive from their interactions with different spaces and socialization agents. In short, through career exploration, children mobilize exploratory behaviors, providing emotional responses. Collaborative ethnography has been shown to be a valid process for research on career exploration as social and emotional learning.